Leaf venation networks of Bornean trees: images and hand-traced segmentations - Blonder, B (University of Oxford, 2018)
The dataset contains images and tracings of leaf venation networks obtained from tree species in Malaysian Borneo. These images are suitable for biological analysis and/or for training of machine-learning algorithms.